Addition of oh8dG to Cardioplegia Attenuated Myocardial Oxidative Injury through the Inhibition of Sodium Bicarbonate Cotransporter Activity - Min Jeong Ji; Kuk Hui Son; Jeong Hee Hong (Antioxidants, 2022)
The biomarker 8-hydroxy-2′-deoxyguanosine (oh8dG) is derived from oxidized nucleic acids or products of oxidant-mediated DNA damage. Enhanced sodium bicarbonate cotransporter (NBC) activity is caused by reactive oxygen species (ROS) production in ventricular myocytes. Thus, we hypothesized that cardioplegia-solution-mediated ROS generation may be involved in the regulation of NBC activity in cardiomyocytes and that oh8dG treatment may modulate ROS and associated NBC activity. Langendorff-free cardioplegia-arrested cardiac strips and cardiomyocytes were isolated to determine the NBC activity and effects of oh8dG on oxidative-stress-mediated cardiac damage markers. We first determined the histidine-tryptophan-ketoglutarate (HTK) solution mediated NBC activity in cardiac strips and cells. The oh8dG treatment attenuated NBC activity in the electroneutral or electrogenic form of NBC. Additionally, exposure to HTK solution induced ROS, whereas co-administration of oh8dG attenuated ROS-mediated NBC activity, reduced ROS levels, and decreased the expression of apoptotic markers and fibrosis-associated proteins in cardiac cells. The oh8dG-administrated cardiac tissues were also protected from enhanced HTK-induced damage markers, heat shock protein 60 and polyADP-ribose. Our results show that oh8dG has a protective role against myocardial oxidative damage and provides a useful treatment strategy for restoring cardiac function.